IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA PADA MATERI ARITMATIKA TERHADAP KEMAMPUAN PEMAHAMAN PESERTA DIDIK - Maysaroh, Ulfa; Pertiwi, Putri; Saputri, Lilis (Jurnal Pendidikan Vokasi dan Seni, 2024)
A The Pancasila learner profile describes the competencies and characters developed in daily life and applied by each learner through educational programs, the Pancasila learner profile, or other extracurricular activities. This study aims to analyze the implementation of the ability of students' understanding in learning arithmetic through efforts to improve the project of strengthening the Pancasila profile through the theme of entrepreneurship. The population in this study were X grade students of Taruna Bangsa High School. The sample is class X students totaling 5 students. Learners' understanding ability is determined through tests, interviews, and documentation used for data collection. This data was then analyzed using descriptive qualitative methods. The results showed that through the Pancasila learner profile strengthening project the understanding of students on Arithmetic material increased. The expected suggestion from the researcher is that the strengthening of the Pancasila learner profile can help improve students' understanding of the learning material being taught.